(untitled) (The International Journal for Scientific Research, 2025)
This research addresses the political conflict and national transformations in Chad after the fall of the First Republic (1975–1990). During this period, the country witnessed a series of coups and armed conflicts between political and military factions, along with foreign interventions, particularly from Libya and France. The phase began with a military coup led by General Félix MALLOUM, followed by a power struggle with HISSENE HABRE, and then the outbreak of the first civil war, which divided the country along regional, ethnic, and religious lines. Several local and international conferences and initiatives (Kano, Lagos, DOUGIA) attempted to achieve national reconciliation, but they failed due to internal divisions and external interferences. The period concluded with the rise of Hissène Habré to power and the subsequent downfall of his regime at the hands of the National Salvation Movement led by IDRISS DEBY in 1990. This stage was characterized by political instability, escalating ethnic conflicts, and the deterioration of economic and social conditions.